1997
DOI: 10.2307/1592143
|View full text |Cite
|
Sign up to set email alerts
|

Various Blood Parameters in Commercial Hens Acutely and Chronically Infected with Mycoplasma gallisepticum and Mycoplasma synoviae

Abstract: Two trials were conducted to study the effects of acute (Trial 1) and chronic (Trial 2) mycoplasma infections on differential leukocyte counts in chickens. The trials initially included either 20 (Trial 1) or 40 (Trial 2) 6-wk-old commercial leghorn chickens negative for antibodies to Mycoplasma gallisepticum (MG) and Mycoplasma synoviae (MS). Chickens were inoculated with F strain MG (FMG), MS (WVU 1853), or both. One group of chickens remained uninoculated and served as a negative control for both trials. Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…Consistent with studies of responses of domestic poultry infected with M. gallisepticum (Branton et al, 1997), the proportions of heterophils and monocytes in wild House Finches showed the most extreme changes as a function of visible signs of mycoplasmal conjunctivitis. Relative levels of heterophils and monocytes were clearly higher among House Finches with clinical signs of MG, and both leukocyte types increased with infection severity (Fig.…”
Section: Leukocytes and Mycoplasmal Conjunctivitissupporting
confidence: 82%
See 2 more Smart Citations
“…Consistent with studies of responses of domestic poultry infected with M. gallisepticum (Branton et al, 1997), the proportions of heterophils and monocytes in wild House Finches showed the most extreme changes as a function of visible signs of mycoplasmal conjunctivitis. Relative levels of heterophils and monocytes were clearly higher among House Finches with clinical signs of MG, and both leukocyte types increased with infection severity (Fig.…”
Section: Leukocytes and Mycoplasmal Conjunctivitissupporting
confidence: 82%
“…Most conclusions concerning the function of avian leukocytes in innate immunity are based on research conducted with domestic poultry (e.g., Branton et al, 1997;Qureshi, 1998;Zulkifli et al, 1999;Campo et al, 2000;Elston et al, 2000), but a growing number of experimental and descriptive studies have examined leukocytes in wild passerines. Leukocyte profiles have been used in recent empirical studies to assess general stress and immunocompetence in wild birds (e.g., Svensson and Skarstein, 1997;Figuerola et al, 1999;Bortolotti et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Live MG vaccines reduce the effects of MG clinical signs and have been shown to replace indigenous strains (Evans et al, 2002). Despite the welldocumented reports concerning the effects of MG vaccination on the blood characteristics and chemistry of layer hens (Branton et al, 1997;Burnham et al, 2003;Peebles et al, 2008Peebles et al, , 2009, only a few reports are available concerning the effects of MG vaccination on the physiological blood gas parameters and acid-base balance of layer hens. In addition, MG-induced effects on the physiological and immunological interactions in layer hens are poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, estimated heterophil numbers increased following stress in infected birds, which is in contrast to the decrease seen in uninfected birds (table 1 ). This pattern makes sense given the role of this cell in the immune system; studies of domestic chickens indicate that heterophils, being phagocytic in nature, are important in the host response to MG infection (Branton et al 1997). A previous survey of leukocyte profiles in MG-infected and uninfected house finches also found that infected birds had greater numbers of heterophils (Davis et al 2004).…”
Section: Discussionmentioning
confidence: 93%